Baseline Assessments of Wildlife Biodiversity Within Selected Areas of Central Visayas, Philippines (Journal of Biodiversity Conservation and Bioresource Management, 2021)
A comprehensive inventory of faunal biodiversity was conducted within three Key Biodiversity Areas of Central Visayas. Mt. Bandilaan Natural Park (MBNP), Balinsasayao Twin Lakes Natural Park (BTLNP), and Rajah Sikatuna Protected Landscape (RSPL). Three primary wildlife groups were surveyed: bats, birds and amphibians. Species diversity and population trends were then analyzed to assess areas of biodiversity importance. RSPL generally had the highest species richness and diversity index while MBNP consistently had the lowest. When pooled. The surveyed areas resulted in a high diversity index and rate of endemicity showing the importance of multiple areas of protection. These findings can be utilized to prioritize habitat protection as well as to serve as a baseline information for future biodiversity inventories.J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 27-34